Morphogenesis of Cymbidium atropurpureum In-Vitro - Subramaniam, Gayathery; Mat Taha, Rosna (Malaysian Journal of Science, 2003)
Shoot tips excised from the orchid, Cymbidium atropurpureum, produced protocorm-like bodies (PLB) on hormone-free Vacin and Went medium and hormone supplemented Vacin and Went (VW) medium. Explants showed the highest PLB formation (63.33%) on the medium supplemented with 5.0 mg/l of α-naphthaleneacetic acid (NAA). The PLBs obtained were regenerated on hormone-free Murashige and Skoog (MS) medium. Besides PLB formation, callus formation from shoot tips was also observed in this study. Pseudobulb, rhizome and root explants produced callus on 1/2 strength MS mdium supplemented with 10 mg/l 2,4-dichlorophenoxyacetic acid and 0.1 mg/l of thiadiazuron. The callus was maintained by sub-culturing in the same medium. Further experiments to determine if the callus obtained is organogenic or embryogenic is in progress.